Innovation of the “Tumbas” marketplace: Policy network analysis in the empowerment of small and medium industries in Mojokerto Regency - Tsabitah Mariyah Dwiyanti; Kalvin Edo Wahyudi (Satwika : Kajian Ilmu Budaya dan Perubahan Sosial, 2025)
Empowering Small and Medium Enterprises (SMEs) through a policy network approach has rarely been studied in depth, particularly in the context of marketplace innovation. This study examines how policy networks contribute to SME empowerment through the "Tumbas" marketplace innovation in Mojokerto Regency. Using a descriptive qualitative approach and Waarden's (1992) seven-dimensional framework of policy networks, this study involved in-depth interviews, observation, and documentation. The results indicate that the "Tumbas" policy network has actors and functions, a collaborative structure, strong institutionalization, functional rules of action, and complementary actor strategies. The Department of Industry and Trade is central to decision-making, while other actors support an inclusive digital ecosystem. Performance achievements exceed targets, reflecting the policy network's success in supporting technology-based local economic empowerment policies. The novelty of this study lies in its comprehensive policy network analysis of regional marketplace innovation, particularly "Tumbas," and in its practical implications for replicating collaborative policy models in other regions.   Pemberdayaan Industri Kecil dan Menengah (IKM) melalui pendekatan jaringan kebijakan masih jarang dikaji secara mendalam, khususnya dalam konteks inovasi lokapasar. Penelitian ini mengkaji bagaimana jaringan kebijakan berkontribusi dalam pemberdayaan IKM melalui inovasi lokapasar “Tumbas” di Kabupaten Mojokerto. Menggunakan pendekatan kualitatif deskriptif dan kerangka tujuh dimensi jaringan kebijakan dari Waarden (1992), penelitian ini melibatkan wawancara mendalam, observasi, dan dokumentasi. Hasil penelitian menunjukkan bahwa jaringan kebijakan “Tumbas” memiliki aktor dan fungsi, struktur kolaboratif, pelembagaan yang kuat, aturan bertindak yang fungsional, serta strategi aktor yang saling melengkapi. Disperindag berperan sentral dalam pengambilan keputusan, sementara aktor lain mendukung ekosistem digital yang inklusif. Capaian kinerja menunjukkan yang melebihi target, mencerminkan keberhasilan jaringan kebijakan dalam mendukung kebijakan pemberdayaan ekonomi lokal berbasis teknologi. Kebaruan dari penelitian ini terletak pada analisis jaringan kebijakan secara komprehensif terhadap inovasi lokapasar daerah khususnya “Tumbas”, serta memberikan implikasi praktis bagi replikasi model kebijakan kolaboratif di wilayah lain.